Malaysian Vehicle License Plate Recognition Using Double Edge Detection - Abu Bakar, Norazhar; Md Nawawi, Mohamad Riduwan; Abdullah, Abdul Rahim; Noordin, Aminurrashid; Musa, Zainolizam; Xian, Oon Cee (2012)
Vehicle plate number is a unique combination of characters and numbers. Hence, it has been used in various application as personal identification such as for parking system identification, security monitoring system and etc. This paper illustrated the double edge detection technique in order to enhance the vehicle plate image, before character recognition process. Firstly, the vehicle image is captured, and then it will be re-sized and cropped until the resolution of image is 300×300. After the re-sized process, First Edge detection is applied to the image. Threshold of black and white are 59 and 60 respectively used to change the image into black and white colour only. Next, Second Edge detection is used to remove the unwanted image and only remain the plate number in white colour. MATLAB software is used in this experiment.